EVALUASI DAN PEMECAHAN MASALAH LALU LINTAS PADA RUAS JALAN PANTURA DI KABUPATEN REMBANG (KALIORI-SLUKE) - Annisa Rachmawati; Gusfina Tryandari; Y.I. Wicaksono; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2014)
Rembang Municipality currently shows significant development in various sectors that predicted will increase travel distribution caused by enormous trip generation and attraction. This condition will impact on the performance of Pantura as a national road network, mainly the segment that pass through this area. Therefore, it is necessary to evaluate the performance of some links and signalized intersections as part of Pantura in Rembang as well as provide suggestions to resolve the problem. The analysis of road and signalized intersections performance refers MKJI 1997, while the proposed treatment refers to Rembang Municipality’s Regional and Spatial Planning Document (RTRW) 2011 - 2031. The result showed that the values of DS in 2013 are 0.486, 0.848, 0.713 and 0.324 respectively at Kaliori Segment, Kartini Park Intersection, Lasem Mosque Intersection and Sluke Segment. The cycle time at each intersection is resetted and the LTOR rule is not applicable in order to improve the intersection performance before the future performance prediction analysis undertaken. In 2020, the number lanes on Sluke should be add up from 2/2 UD (DS = 0.849) to 6/2 D (DS = 0.330). The construction of Rembang Urban Ring Roads in 2016-2020 could be decrease the DS value at Kartini Park Intersection in  2021 (DS = 0.669), but in 2028 the DS has reached 0.909. Therefore, the trafiic signal phase must be adjusted to decline DS value to 0,462 in 2021 and 0,676 in 2028. The Lasem Urban Ring Road in 2024 decrease DS value at Lasem Mosque Intersection to 0,667 thus 0,807 in 2028. After the Rembang Outer Ring Road and Rembang Urban Ring Road officially open for public, the DS of Kaliori Segment and Kartini Park Intersection could be decrease upto 0.687 and 0,517 respectively. According to Rembang Municipality’s Regional and Spatial Planning Document, the Rembang Outer Ring Road will be operationalized in 2026 and the Lasem Urban Ring Road in 2024. However, this research suggest that this plan should be rescheduled to 2019 for Rembang Outer Ring Road and 2021 for Lasem Urban Ring Road.